If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(5a + -4) = 15 + -8a Reorder the terms: 7(-4 + 5a) = 15 + -8a (-4 * 7 + 5a * 7) = 15 + -8a (-28 + 35a) = 15 + -8a Solving -28 + 35a = 15 + -8a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '8a' to each side of the equation. -28 + 35a + 8a = 15 + -8a + 8a Combine like terms: 35a + 8a = 43a -28 + 43a = 15 + -8a + 8a Combine like terms: -8a + 8a = 0 -28 + 43a = 15 + 0 -28 + 43a = 15 Add '28' to each side of the equation. -28 + 28 + 43a = 15 + 28 Combine like terms: -28 + 28 = 0 0 + 43a = 15 + 28 43a = 15 + 28 Combine like terms: 15 + 28 = 43 43a = 43 Divide each side by '43'. a = 1 Simplifying a = 1
| x-5=6(3x+8) | | (x/9)*6 | | 6y=-6x-4 | | -2(4+5n)-5=-83 | | 5x-15-6x=6-6x/54 | | 1.4(1+0.5x)=-7 | | -16=-11-5(2a-3) | | 5x-15-6x=6-x/9 | | 2(g-2)-4=2(2g-3) | | 3.50x+36=5x | | -6=-2/x | | a=-10.6-1.5a | | 2x-16=2x-8 | | 10.3x+1=2x+4 | | 2lnx-ln(2x-7)=ln(9x)-ln(x-2) | | -14k^2-280=0 | | 3z-1z+2z-30=70 | | x+10=-100 | | 9x+10=8+8x | | 5/(x-4)=0 | | -2(2x-5)=2(X-7) | | 3y-1z+2z-30=70 | | -10x^2+22x+12=0 | | 13=p-(-15) | | 5x(4-x)=9-(x-6) | | -10y-5y=120 | | 2cos(0.5)-1=0 | | 7=b+2 | | r^2-10x-50=0 | | -6x-1x=56 | | -4/4=x | | 96x-9/2x^2 |